Pad foundation construction for project single storey house at Kampung Pulau Kapas, Panji 15200 Kota Bharu, Kelantan - Mohd Sudin, Muhd Khairul Ikhwan (Faculty Of Architecture, Planning And Surveying, 2019)
Pad foundation is generally shallow foundation. The mam function of foundation is to give support for structures, transferring the load to layers of soil or rock that have a good sufficient bearing capacity and have a match settlement characteristics. They can be used to help to avoid settlement and another movements of structures and can grant construction on ground that might have unbalance bearing capacity. Foundation usually located at a shallow depth, also be used as deep foundation depending on the loads to be transferred and condition of the subsoil.